Antibacterial Mechanism of Chitosan and its Applications in Protection of Plant from Bacterial Disease: Mini Review - Li1, B.; Shan1, C.L.; Ge1, M.Y.; Wang1, L.; Fang2, Y.; Wang3, Y.L.; Xie1, G.L.; Sun3, G.C. (Asian Journal of Chemistry, 2013)
Chitosan has showed strong antibacterial activity against a variety of gram-negative and gram-positive bacteria. This paper reviews current and potential agricultural applications of chitosan in preventing bacterial disease in plants according to recent data found in the literature. In particular, the possible and accepted antibacterial mechanisms for chitosan are presented and discussed.